A new genus and species of Baetidae (Insecta, Ephemeroptera) from Brazil - Salles, Frederico Falcão (Arquivos do Museu Nacional, 2021)
Tupiara gen.nov. (Ephemeroptera, Baetidae) is described from one species, Tupiara ibirapitanga sp.nov., based on nymphs and the male adult. The nymphs can be distinguished by the following combination of characteristics: relatively narrow mandibles with partially fused incisors; left mandible with external incisor provided with multiple denticles apically and on inner margin, and with an obtuse angle between incisors and anterior margin; right prostheca basally bifurcated; rectangular, apically rounded paraglossa; second segment of labial palps distomedially pronounced and rounded; dorsal margin of femora conspicuously sclerotized; tarsal claws with two rows of denticles; and terga without scales or scale bases. Adults can be diferentiated by having the turbinate portion of the compound eyes elliptical and relatively narrow; hindwings with acute process on basal one-third and two unbranched longitudinal veins; and an internally curved, narrow-elongate third segment of the genital forceps. The possible relationship between Tupiara gen.nov. and Andesiops, as well as the differences between the two genera, are discussed. Representatives of Tupiara ibirapitanga sp.nov. were mainly collected from well-preserved areas and at relatively high elevations in the states of Amazonas, Minas Gerais, and Rio de Janeiro, Brazil. Aspects of the emergence of nymphs of the species are related.